7 will of the Malay Kings: An analysis on the history and Malaysian constitution - Adam, Ramlah (2014)
On 5th of August 2011, Raja Nazrin Shah, the Crown Prince of Perak had reminded the people regarding the Will of the Malay Kings, which were written when they unanimously signed their support in favoring the independence of Malay Land Federation on the 31st of August 1957.These will by itself was an evidence of their attention on the future of their people in a free country.This will, however, had never been exposed to the public as a reminder.This is because the Monarchy institution had been accepted undisputedly as a ruling and governing body, as well as the social culture of the people.However, with the latest development, the status of the Malay Kings is mentioned wrongly in the modern as well as social media, thus jeopardizing their rightful status. Thus, the Kings themselves had to step forward in defending this institution, by stating their status both in the constitution and societal level.One of the way of doing this is to remind the people about the 7 Will of the Malay Kings.